EVALUASI KONDISI MESIN BUBUT HARIZON T300 MENURUT METODE SCHLESINGER SEBAGAI ACUAN DALAM MELAKUKAN TINDAKAN PERAWATAN - Frans Mangngi (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2018)
To ensure that a lathe still has a high performance and accuracy, it is necessary to evaluate the condition of the machine. The results of the evaluation are not only used to determine the performance and accuracy of the machine but more than that can be used to determine the maintenances and repairs actions more precisely, therefore the condition of the machine can be returned to a better state. The aims of the reserach was to evaluate the condition of lathe machine Harizon T300 brand that exists in the Laboratory of Maintenance and repair of Mechanical Engineering Department of State Polytechnic of Kupang; The results of this evaluation will serve as a reference in performing appropriate maintenance actions against the machine. The evaluation method and procedure used is based on standard test chart according to Schlesinger method. It was found that, from the 8 test components of Harizon T300 lathes, only two test components that still met the standards of geometric accuracy are: (1). Centre sleave for true running, and (2). Centre point for true running; While the other 6 components of testing have not met the required standards, namely: (1). The flatness of the bed, (2). Work spindle parallel with the bed in a vertical and horizontal plane, (3). Work spindle parallel with the bed in the vertical and horizontal plane, (4). the axis of centers parallel with the bed in the vertical plane, (5). Tailstock sleeve parallel with bed vertical and horizontal plane, and (6). Tailstock guide ways parallel with the movement of the carriage; Thus the conclusion of this research is the Harizon T300 lathes that used as a sample of this research was not standard anymore and needs to be reconditioned.